Experimental and Numerical Study of a Microcogeneration Stirling Unit under On–Off Cycling Operation - Gianluca Valenti; Aldo Bischi; Stefano Campanari; Paolo Silva; Antonino Ravidà; Ennio Macchi (Energies, 2021)
Stirling units are a viable option for micro-cogeneration applications, but they operate often with multiple daily startups and shutdowns due to the variability of load profiles. This work focused on the experimental and numerical study of a small-size commercial Stirling unit when subjected to cycling operations. First, experimental data about energy flows and emissions were collected during on–off operations. Second, these data were utilized to tune an in-house code for the economic optimization of cogeneration plant scheduling. Lastly, the tuned code was applied to a case study of a residential flat in Northern Italy during a typical winter day to investigate the optimal scheduling of the Stirling unit equipped with a thermal storage tank of diverse sizes. Experimentally, the Stirling unit showed an integrated electric efficiency of 8.9% (8.0%) and thermal efficiency of 91.0% (82.2%), referred to as the fuel lower and, between parenthesis, higher heating value during the on–off cycling test, while emissions showed peaks in NOx and CO up to 100 ppm but shorter than a minute. Numerically, predictions indicated that considering the on–off effects, the optimized operating strategy led to a great reduction of daily startups, with a number lower than 10 per day due to an optimal thermal storage size of 4 kWh. Ultimately, the primary energy saving was 12% and the daily operational cost was 2.9 €/day.